Estimasi Heritabilitas Bobot Badan Keturunan F1 Ayam Kampung Periode Starter - Rajab, Rajab; Matatula, Michel Johan; Ririmase, Pieter Melianus (Universitas Islam Negeri Alauddin Makassar, 2025)
The study aimed to estimate the heritability of body weight in first-generation (F1) native chickens during the starter period. A total of 100 native chickens, F1 offspring from the natural mating of 4 males with 5 females each, were used as research samples. Chicken body weight was measured weekly for body weight data at one day, 1, 2, 3, and 4 weeks of age. Descriptive statistical analysis by calculating the mean, standard deviation (SD), and coefficient of variation (CV) was used to describe the body weight of the native chickens during the starter period. To determine the estimated heritability, a full-sib mating design analysis model was used. The results showed that the average body weight of the native chickens during the F1 generation was 26.51 g at one day of age, increasing with age to 177.34 g at 4 weeks of age, with estimated heritability ranging from 0.02 to 0.30, which is included in the low to moderate category. The use of starter period body weight as a selection criterion is more efficient in producing high genetic improvement for traits related to meat production.